2019
DOI: 10.1002/dmrr.3120
|View full text |Cite
|
Sign up to set email alerts
|

Higher pulse pressure predicts initiation of dialysis in Japanese patients with diabetes

Abstract: Aims To determine incidence and predictors of starting dialysis in patients with diabetes emphasizing blood pressure variables. Methods A nationwide database with claim data on 18 935 people (15 789 men and 3146 women) with diabetes mellitus aged 19 to 72 years in Japan was used to elucidate predictors for starting dialysis. Initiation of dialysis was determined from claims using ICD‐10 codes and medical procedures. Using multivariate Cox modelling, interactions between glycaemic and blood pressure values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…80 In the J-DOIT3 study, intensive therapy with treatment targets of HbA1c <6.2%, blood pressure < 120/75 mmHg, and low-density lipoprotein (LDL) cholesterol <80 mg/dL significantly reduced the onset and progression of nephropathy and retinopathy by 32% and 14%, respectively, showing that comprehensive management is effective in preventing these complications. 81 Studies have shown that high pulse pressure (PP) is an independent risk factor of dialysis 82 and severe retinopathy 83 in patients with diabetes. Since high PP indicates the existence of arteriosclerosis, these results suggest that comprehensive management of hypertension and dyslipidaemia is critical to improve the prognosis of diabetes by preventing the onset and progression of arteriosclerosis.…”
Section: Type 2 Diabetes Mellitus: Recent Treatment Pattern Management Of Complications and Comparative Effectiveness Studiesmentioning
confidence: 99%
“…80 In the J-DOIT3 study, intensive therapy with treatment targets of HbA1c <6.2%, blood pressure < 120/75 mmHg, and low-density lipoprotein (LDL) cholesterol <80 mg/dL significantly reduced the onset and progression of nephropathy and retinopathy by 32% and 14%, respectively, showing that comprehensive management is effective in preventing these complications. 81 Studies have shown that high pulse pressure (PP) is an independent risk factor of dialysis 82 and severe retinopathy 83 in patients with diabetes. Since high PP indicates the existence of arteriosclerosis, these results suggest that comprehensive management of hypertension and dyslipidaemia is critical to improve the prognosis of diabetes by preventing the onset and progression of arteriosclerosis.…”
Section: Type 2 Diabetes Mellitus: Recent Treatment Pattern Management Of Complications and Comparative Effectiveness Studiesmentioning
confidence: 99%
“…It is the SBP which is raised; that augments pulse pressure and such pulsatile flow lead to end organ damage to kidney that manifests as DN. [16]…”
Section: Discussionmentioning
confidence: 99%
“…8 Details of the claims data and classifications were described elsewhere. [8][9][10] Patients aged 19-72 years who were followed for at least 3 years from 1 April 2008 to 31 March 2013 without a history of dialysis based on dialysis-related procedures performed in the 1 year before follow-up were included in this analysis and continued to be followed until 31 September 2016. For the present study, we examined data on 296 121 individuals.…”
Section: Study Participantsmentioning
confidence: 99%